Deformačně-napěťová analýza povrchové náhrady kyčelního kloubu - Vosynek, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
V současné době je aloplastika kyčelního kloubu zasažena mnoha inovačními prvky. Povrchová náhrada kyčelního kloubu zažívá značný rozmach. Používá se především pro ošetření mladých a aktivní lidí, u kterých se předpokládá následná revize klasickou totální náhradou. Cílem této práce bylo určit deformačně-napěťové stavy v kyčelním kloubu s aplikovanou totální povrchovou náhradou pro různá ustavení femorální komponenty vůči stehenní kosti a srovnat je s deformačně-napěťovými stavy zjištěnými u fyziologického kloubu. Řešená soustava se skládá z křížové, pánevní, stehenní kosti, svalů, umělé jamky a femorální komponenty. Výpočty byly provedeny v konečnoprvkovém systému ANSYS. Geometrický model kostí byl vytvořen pomocí řezů získaných z počítačové tomografie. Zatížení odpovídá stoji na jedné dolní končetině. V práci je prezentována srovnávací analýza a výsledky deformačně-napěťových analýz, z nichž vyplývá celá řada velmi zajímavých poznatků.

Today is the surface hip repacement very often surgery becouse of new studies and improvements. For young and active people it's the best way to delay implantation of a total hip replacement. The objective of this study was to perform finite-element analyses of computational model of the partial/total surface replacement, conventional partial/total replacement and physiological hip joint. We obtained strain-stress states from these analyses. All results were compared one another and then were confronted with results of the physiological hip joint. The three-dimensional computational model consists of these components: sacral, pelvic and femoral bone, muscles, artificial socket, and surface hip replacement. We were using FEM system ANSYS. The geometrical models of bones were generated by means of computed tomography (CT) images. The FE model of bone reflects two types of the bone tissues (trabecular and cortical bone) and muscles which are important when standing on one leg. The model of the muscle corresponds to isometric contraction. The implants material and bone tissues were modelled as isotropic linear elastic material. The model was loaded by force, corresponding to load by standing on one leg.
Strain-stress analysis of the surface replacement of the hip joint
Keywords: Povrchová náhrada kyčelního kloubu; MKP; ANSYS; biomechanika; Hip resurfacing; FEM; ANSYS; Biomechanics